The Relationship between Mosquito Nest Eradication Practices (3M Plus) and the Incidence of Dengue Hemorrhagic Fever: A Case Control Study in Bengkulu City, Indonesia - Fauzi, Yusran; Marya Sari, Fikitri (Yayasan Darussalam Bengkulu, 2023)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical and subtropical countries, including Indonesia, where periodic outbreaks are strongly associated with environmental conditions and community behaviors. This study aimed to analyze the relationship between mosquito nest eradication through the implementation of 3M Plus draining, closing, recycling, and additional preventive practices and the incidence of DHF in the working area of the Beringin Raya Public Health Center, Bengkulu City. A case-control survey design was employed involving 72 respondents, consisting of 36 cases and 36 controls selected through total sampling. Data were collected using structured questionnaires and analyzed with the Chi-Square test to assess associations, while odds ratios with 95% confidence intervals were calculated to determine risk estimates. The findings revealed that 43.1% of respondents demonstrated poor implementation of 3M Plus and 56.9% showed good practices. Bivariate analysis indicated a significant relationship between mosquito nest eradication behaviors and DHF incidence (χ² = 6.977; p = 0.017), with individuals demonstrating poor preventive practices being 3.64 times more likely to contract DHF compared to those with good practices. These results emphasize the critical role of consistent environmental management and community participation in minimizing vector breeding and reducing disease transmission. The novelty of this study lies in providing localized empirical evidence from Bengkulu City, where research on dengue prevention remains limited, thereby contributing to the evidence base for community-based vector control programs. The implications suggest that health centers and policymakers should strengthen health promotion, monitoring, and community engagement strategies to improve adherence to 3M Plus as an effective measure for reducing dengue incidence in endemic areas.